Issues of concern in road transport system in Nigeria (2006)
The road transport system in Nigeria has played a major role in the socio-economic development of the country. The road mode still remains the dominant and most elaborate of all forms of transport in the country today. However, several issues are of concern to both the operators and users of road transport system in Nigeria. These include condition of roads and its funding, road traffic accidents and vehicular air pollution. For example, 54 per cent of the road network in Nigeria is still in poor condition with, an annual cost of N133.8 billion (INR = N 2.92) to the Nigerian economy. About N300 billion is needed in the next ten years to bring the total network of roads in the country into fairly good condition. In the same vein, deaths from road traffic accidents have also been staggering. For example, between 1960 and 2001 more than 2,50,000 people have lost their lives in road traffic accidents. The growth in vehicular traffic coupled with rapid urbanization has led to increase in Vehicular Air Pollution (VAP) making Nigeria's air quality one of the worst in the world. Therefore, a range of integrated approach is needed to bring sanity into Nigerian road transport system so as to enhance the effective mobility of people as well as the socio-economic development of the country.